Differential effects of mass-loading the eardrum and stiffening the middle ear on wideband absorbance - Lewis, James D.; Rutherford, Alicia; Stanford, Kathleen E. (The Journal of the Acoustical Society of America, 2024)
The current work investigated the effects of mass-loading the eardrum on wideband absorbance in humans. A non-invasive approach to mass-loading the eardrum was utilized in which water was placed on the eardrum via ear canal access. The mass-loaded absorbance was compared to absorbance measured for two alternative middle ear states: normal and stiffened. To stiffen the ear, subjects pressurized the middle ear through either exsufflation or insufflation concurrent with Eustachian tube opening. Mass-loading the eardrum was hypothesized to reduce high-frequency absorbance, whereas pressurizing the middle ear was hypothesized to reduce low- to mid-frequency absorbance. Discriminant linear analysis classification was performed to evaluate the utility of absorbance in differentiating between conditions. Water on the eardrum reduced absorbance over the 0.7- to 6-kHz frequency range and increased absorbance at frequencies below approximately 0.5 kHz; these changes approximated the pattern of changes reported in both hearing thresholds and stapes motion upon mass-loading the eardrum. Pressurizing the middle ear reduced the absorbance over the 0.125- to 4-kHz frequency range. Several classification models based on the absorbance in two- or three-frequency bands had accuracy exceeding 88%.